MANAJEMEN PROGRAM PENDIDIKAN KADER MUBALIGH DI ASRAMA PENGHAFAL QURAN RABBANI - M. Raihan Matondang; Hasrian Rudi Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to determine the Management of the Missionary Cadre Education Program in the Rabbani Quran Memorizer Dormitory and the objectives of the activities in this missionary cadre program for the students. The Rabbani Quran Memorizer Dormitory is one of the dormitories that runs a preacher cadre program designed to develop the character of its students under the direct guidance of the Dormitory Director and the ustadz. This Mubaligh Cadre Program takes place every Sunday, specifically after the congregational Isha prayer, with students taking turns leading the activity. This research employs a qualitative method with a descriptive approach, focusing on observing ongoing events and processes. Data collection techniques used in this research include interviews, observations, and documentation. The data analysis technique in this research uses the Miles and Huberman data analysis technique. The description of the results of this research is the preacher cadre program to shape the characteristics of students in the Rabbani Quran Memorizer Dormitory. The steps in forming the characteristics of the students in this missionary cadre program, start from planning the missionary cadre education program, implementing the missionary cadre education program, as well as supervising the missionary cadre education program.